Predictive factors for failure of high flow nasal cannula among children with lower respiratory tract infection: A single center retrospective observational study - Phanthila Sitthikarnkha; Rattapon Uppala; Apichaya Thiraratananukulchai; Prapassara Sirikarn; Leelawadee Techasatian; Suchaorn Saengnipanthkul; Sirapoom Niamsanit (PLoS ONE, 2025)
Background and objective Lower respiratory tract infection (LRTI) is a leading cause of childhood hospitalization worldwide, with high-flow nasal cannula (HFNC) therapy commonly employed as a non-invasive respiratory support method. Determining early predictors of HFNC failure is crucial for timely intervention and reducing associated morbidity and mortality. Methods We retrospectively reviewed the medical records of hospitalized children aged 1 month to 18 years with LRTI who received HFNC from January 2016 to December 2021. We aimed to evaluate predictive factors for HFNC failure and identify optimal cutoffs from the AUROC (AUROC). Results One hundred and sixteen children with LRTI applied to HFNC were included in this study. Most of them (90.5%) were diagnosed with pneumonia as a principal diagnosis, and 68.9% had co-morbidities. Of those, 18 patients (15.5%) needed escalation to intubation and were defined as HFNC failure. The early predictive parameters associated with HFNC failure were pulse rate at 2 hours and SpO2/FiO2 ratio at 4 hours. AUROC analysis for the predictive parameter of HFNC failure showed cut-off values of S/F ratio at 4 hours after HFNC therapy was lower than 238 (AUC 0.89, 95%CI: 0.78–0.99). Conclusion SpO2/FiO2 at 4 hours after initiating HFNC appeared to be a predicting value for early detected failure for HFNC therapy in children with LRTI. Close monitoring and swift management adjustments are recommended for children exhibiting these risk factors to enhance outcomes.